HANNA ARENDT’S VIEW ON POLITICAL POWER AND VIOLENCE - Штерн, В. Ю. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The author considers the problem of correlation between power and violence formulated by an outstanding western politologist Hanna Arendt. Arendt reveals creative potential of power through insurance and guaranteeing of human rights, providing conditions for optimum balance of the public and the private, achievement of freedom. Hanna Arendt characterizes the creative function of power as the main in the social-political development.